Spectropolitic: image and hauntology in the contemporary visual culture - Gómez Gabriel, Núria (2020)
In his book Spectres of Marx, Jacques Derrida puts forth the term hauntology [hantologie] as an epistemic turn dedicated to thinking about the ways in which technology materialises memory that stems from the premise that nothing enjoys a purely positive existence, and that, as music critic Mark Fisher reminds us in his reflections on depression, everything that exists is possible only on the basis of a series of absences that precede it, surround it, and allow it to possess coherence and intelligibility. This article presents the concept of spectropolitics in order to observe how certain events of late capitalism and financial abstractions reverberate in the collective psyche and transform into spectral apparitions. Far from an understanding of the obscurantist spectre as something real, we understand its presence as a sign or a metaphor of the vision that acts as a clarifying figure with a specifically ethical and political potential. Likewise, the new materialities of the fleeting, fugitive and subjective visuality of our present (dominated by the internet and the processes of psychic privatisation) interrogate us about the collectivities that are organised in the ways of seeing of contemporary societies and in the traces of the power structures that underlie them.